Allies, Pearl Harbor to D-Day - Eisenhower, John S. D (Da Capo Press, 2000)
"A satisfying history, at once colorful and clear . . . [of] of the grand strategy of the war".--"The New York Times Book Review". "Already a proven military historian, the son of General Dwight Eisenhower enhances his reputation with this study".--"Choice"